Flexible 3D nanofiber-based SERS biosensor for detection of miRNA-223-3p in early Laryngeal Cancer diagnosis - Martino, Sara; Yilmaz, Deniz; Tammaro, Chiara; Misso, Gabriella; Esposito, Alessandro; Falco, Michela; Cossu, Alessia Maria; Lombardi, Angela; Amler, Evzen; Divin, Radek; Giannetti, Ambra; Scrima, Marianna; et al. (Talanta, 2025)
MicroRNAs (miRNAs) are small non-coding RNAs (18-22 nucleotides) that regulate gene expression and are associated with various diseases, including Laryngeal Cancer (LCa), which has a high mortality rate due to late diagnosis. Traditional methods for miRNA detection present several drawbacks (time-consuming steps, high cost and high false positive rate). Early-stage diagnosis and selective detection of miRNAs remain challenging. This study proposes a 3D flexible biosensor that combines nanofibers (NFs), gold nanoparticles (AuNPs), and an inverse molecular sentinel (iMS) for enzyme-free, SERS-based detection of miRNA-223-3p, evaluated as a potential LCa biomarker. The electrospun flexible nanofibers decorated with AuNPs enhance Raman signal. Selective detection of miRNA-223-3p is achieved by immobilizing an iMS-DNA probe labeled with a Raman reporter (Cyanine 3) on the AuNPs. The iMS distinctive stem-and-loop structure undergoes a conformational change upon interaction with the miRNA-223-3p, producing an "on to off" SERS signal. The proposed sensor demonstrated a linear detection range from 10 to 250 fM, with a limit of detection (LOD) of 19.50 ± 0.05 fM. The sensor selectivity was confirmed by analyzing the SERS signal behaviour in the presence of both Non-complementary miRNA and miRNA with three mismatched base pairs. This easily fabricable sensor requires no amplification and offers key advantages, including sensitivity, flexibility, and cost-effectiveness.
Keywords: MicroRNAs; Gold; mikro RNA; Spectrum Analysis, Raman; nádory hrtanu; Ramanova spektroskopie; biosenzitivní techniky; Laryngeal Neoplasms; zlato; limita detekce; Biosensing Techniques; kovové nanočástice; Metal Nanoparticles; lidé; nanovlákna; Humans; Nanofibers; Limit of Detection; Early Detection of Cancer; časná detekce nádoru